Plxdc2 is a mitogen for neural progenitors - MURPHY, PAULA; MITCHELL, KEVIN (My University, 2011)
The development of different brain regions involves the coordinated control of proliferation and cell fate specification along and across the neuraxis. Here, we identify Plxdc2 as a novel regulator of these processes, using in ovo electroporation and in vitro cultures of mammalian cells. Plxdc2 is a type I transmembrane protein with some homology to nidogen and to plexins. It is expressed in a highly discrete and dynamic pattern in the developing nervous system, with prominent expression in various patterning centres. In the chick neural tube, where Plxdc2 expression parallels that seen in the mouse, misexpression of Plxdc2 increases proliferation and alters patterns of neurogenesis, resulting in neural tube thickening at early stages. Expression of the Plxdc2 extracellular domain alone, which can be cleaved and shed in vivo, is sufficient for this activity, demonstrating a cell non-autonomous function. Induction of proliferation is also observed in cultured embryonic neuroepithelial cells (ENCs) derived from E9.5 mouse neural tube, which express a Plxdc2-binding activity. These experiments uncover a direct molecular activity of Plxdc2 in the control of proliferation, of relevance in understanding the role of this protein in various cancers, where its expression has been shown to be altered. They also implicate Plxdc2 as a novel component of the network of signalling molecules known to coordinate proliferation and differentiation in the developing nervous system.
PUBLISHED
Keywords: Neuroscience; Plxdc2; Genes & Society